2019
DOI: 10.1038/s41467-019-11452-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic landscape of squamous cell lung cancer

Abstract: How genomic and transcriptomic alterations affect the functional proteome in lung cancer is not fully understood. Here, we integrate DNA copy number, somatic mutations, RNA-sequencing, and expression proteomics in a cohort of 108 squamous cell lung cancer (SCC) patients. We identify three proteomic subtypes, two of which (Inflamed, Redox) comprise 87% of tumors. The Inflamed subtype is enriched with neutrophils, B-cells, and monocytes and expresses more PD-1 . Redox tumours are enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 79 publications
8
76
1
Order By: Relevance
“…For example, one of the most enriched biological processes seen in our NRF2 signature is that of extracellular matrix (ECM) signalling. Recent proteogenomic work from squamous cell lung cancer [47] noted that somatic mutations of NFE2L2/KEAP1 are enriched for transcriptional programs in ECM similar to the data presented here. Open questions include whether the cancer cell exerts an outward influence on the ECM by increasing NRF2 signalling and creating a protumorigenic environment, or is it an inward effect, with the ECM altering the biology of the cancer cell.…”
Section: Discussionsupporting
confidence: 81%
“…For example, one of the most enriched biological processes seen in our NRF2 signature is that of extracellular matrix (ECM) signalling. Recent proteogenomic work from squamous cell lung cancer [47] noted that somatic mutations of NFE2L2/KEAP1 are enriched for transcriptional programs in ECM similar to the data presented here. Open questions include whether the cancer cell exerts an outward influence on the ECM by increasing NRF2 signalling and creating a protumorigenic environment, or is it an inward effect, with the ECM altering the biology of the cancer cell.…”
Section: Discussionsupporting
confidence: 81%
“…The Fructose-Bisphosphatase 1 (FBP1) is a rate-limiting enzyme in gluconeogenesis, which is suppressed in kidney tumors and thus feeds ccRCC; FBP1 is associated with impaired cell proliferation, glycolysis and the pentose phosphate pathway in ccRCC in a catalytic-activity-independent manner via direct interaction with the HIF inhibitory domain 18 . PSAT1 is up-regulated in many cancers and acts as an oncogene that exerts a vital role in cancer progression and metastasis 19 21 . Interestingly, through mining public database and RT-qPCR, we found that PSAT1 in ccRCC patients is down-regulated compared with normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer represents the leading cause of worldwide cancer‐related death (Ferlay et al., 2015). It is an aetiologically multifactorial disease, including genetic and environmental factors (Stewart et al., 2019). During tumour development, multiple immune evasion mechanisms may lead to insufficient cancer immunosurveillance process (Vinay et al., 2015).…”
Section: Introductionmentioning
confidence: 99%